Looking Out, Looking In, 15th Edition - Ronald B. Adler; Russell F. Proctor II (Cengage Learning, 2016)
A longtime favorite with millions of students and instructors, LOOKING OUT, LOOKING IN, 15th Edition maintains its market-leading tradition of linking the latest research and theory to readers' everyday lives. Its user-friendly approach motivates students to learn and apply communication principles in both personal relationships and on the job. Expanded emphasis on social media includes an all-new chapter devoted to the role of mediated communication in interpersonal relationships as well as integrated coverage throughout the book. Diverse examples, new readings, compelling cartoons, lively photos, and popular culture references bring principles to life. Thought-provoking prompts in every section help enhance understanding. Hands-on activities help students put what they learn into action. The result: greater student engagement and success.